Pembelajaran Berbasis Proyek Menggunakan Aplikasi Zoom Untuk Meningkatkan Pemahaman dan Keterampilan Berpikir Kreatif Siswa SD (Penelitian Deskriptif Kualitatif Pada Materi Komponen Ekosistem Di Kelas V SDN Pasarean) - Nababan, Nurlela; Sudin, Ali; Sujana, Atep (Jurnal Pena Ilmiah, 2021)
The conventional learning methods have always been applied to science learning that makes students passive so that their thinking process becomes slow and not creative. Project-based learning is an alternative learning model that is suitable for use in science learning. This study realized to increase students' understanding and creative thinking skills in science learning, especially ecosystem component materials. The method used in this study is descriptive qualitative. The results obtained in this study are the implementation of project-based learning using the zoom application is very popular and fosters enthusiasm for learning for students, there is an increase in students' understanding of the ecosystem component material where the pretest results show 73% of students do not meet the criteria while the posttest results from 87% of students get a good category. In addition, the products made by students show that project-based learning can improve students' creative thinking skills.